Polyethylene and Poly(Ethylene-Co-1-Octadecene) Composites with Tio 2 Based Nanoparticles by Metallocenic "In Situ" Polymerization - Rabagliati-Canessa, F; Zapata-Ramirez, P (Elsevier Ltd, 2013)
Ethylene homopolymer and ethylene-co-1-octadecene copolymers with 0.063 mol/L (LLDPE-1) and 0.38 mol/L (LLDPE-2) were synthesized by a metallocenic catalyst in the presence of titanium dioxide (TiO2) nanoparticles (?10 nm), producing "in situ" composites. The TiO2 nanoparticles synthesized by the sol-gel method were used either as-synthesized or modified organically on the surface with hexadecyltrimethoxysilane (Mod-TiO2), with a final concentration in the polymers of 3 and 5 wt%. For polymerizations without nanoparticles, the catalytic activity increased with the incorporation of the octadecene as compared with ethylene homopolymerization. Moreover, the surface functionality of nanoparticles and the presence of a comonomer had some influence on the catalytic behavior, resulting in greater activity when Mod-TiO2 was used than that obtained with TiO2 or the pure system when ethylene is homopolymerized. In copolymerization, an effect on the catalytic behavior was not observed. The dispersion of the nanoparticles was studied by transmission electron microscopy (TEM). There was better dispersion when Mod-TiO2Nps were incorporated into PE, although for LLDPE-2/TiO2 nanocomposites the nanoparticles were not well distributed and certain agglomeration zones were mainly observed. Regarding the thermal properties of the composites, the incorporation of the nanoparticles enhanced the thermal stability of the polymers, increasing by ca. 25 C the maximum decomposition temperature of the matrix as compared with virgin polymers. The final effect of the nanoparticles on the mechanical properties will depend on the matrix used. The addition of TiO2 nanoparticles did not modify the mechanical properties of the PE/TiO2 and LLDPE-1/TiO2 (low octadecene incorporation) matrix, although in polymers with high comonomer incorporation (LLDPE-2/TiO2) an increase of Young s modulus and yield stress by ca. 50% was achieved compares to neat copolymer (LLDPE-2). Our results give relevant information about the effect of polymer microstructure and of the surface functionality of nanoparticles on the catalytic system and on the final properties for in situ composites. The morphology of the nanocomposites was also studied, and it was found that the presence of particles in the PE increased the number of spherulites, therefore the nanoparticles act as nucleating agents. The dynamic-mechanical properties confirm the effect on the mechanical behavior of nanocomposites, that nanoparticles only affect the storage modulus (E?) of the LLDPE-2 matrix. © 2013 Elsevier Ltd. All rights reserved.